Oral health-related quality of life in individuals with severe asthma - Brasil-Oliveira, Rebeca (J Bras Pneumol, 2021)
OBJECTIVE: To evaluate oral health-related quality of life (OHRQoL) among individuals with severe asthma, comparing it with that observed among individuals with mild-to-moderate asthma and individuals without asthma. METHODS: We conducted a cross-sectional study of 125 individuals: 40 with severe asthma; 35 with mild-to-moderate asthma; and 50 without asthma. We calculated the decayed, missing, and filled teeth (DMFT) index, as well as the Periodontal Screening and Recording index, and determined the stimulated salivary flow rate. We applied three structured questionnaires: the 14-item Oral Health Impact Profile (OHIP-14); the Medical Outcomes Study 36-Item Short-Form Health Survey, version 2 (SF-36v2); and the Work Ability Index (WAI). RESULTS: Periodontitis and reduced salivary flow were both more common in the severe asthma group than in the mild-to-moderate asthma and no-asthma groups. In addition, the WAI scores were lower in the severe asthma group than in the mild-to-moderate asthma and no-asthma groups, as were the scores for all SF-36v2 domains. The individuals with severe asthma also scored lower for the OHIP-14 domains than did those without asthma. Although the mean DMFT index did not differ significantly among the groups, the mean number of missing teeth was highest in the severe asthma group. Strong correlations between the SF-36v2 Component Summaries and poorer OHRQoL were only observed in the severe asthma group. CONCLUSIONS: Severe asthma appears to be associated with poorer oral health, poorer OHRQoL, a lower WAI, and lower scores for SF-36v2 domains.